1984
DOI: 10.1136/hrt.51.5.508
|View full text |Cite
|
Sign up to set email alerts
|

Doppler echocardiographic features of coronary arteriovenous fistula. Complementary roles of cross sectional echocardiography and the Doppler technique.

Abstract: SUMMARYThe Doppler echocardiographic features of coronary arteriovenous fistula were investigated in eight patients with left or right coronary arteriovenous fistulas who had a continuous heart murmur in the upper precordial area and whose diagnoses were confirmed by coronary angiography. In four patients the dilated lumen of the coronary arteriovenous fistula was visualised by cross sectional echocardiography. Of these, three showed abnormal unidirectional continuous flow signals with broad velocity spectra i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

1986
1986
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(8 citation statements)
references
References 5 publications
(1 reference statement)
0
8
0
Order By: Relevance
“…It is not rare that color Doppler TTE cannot detect flow signal in the distal portion of CAF. Previous studies have indicated that it was extremely hard to depict CAF by TTE, particularly in the cases having the left anterior descending coronary artery as the feeding vessel 6, 7, 9 . In addition, the CAF cases with the drainage site in the pulmonary artery were also reported to be difficult to fully detect by TTE, because the feeding coronary artery was not dilated 8, 10 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is not rare that color Doppler TTE cannot detect flow signal in the distal portion of CAF. Previous studies have indicated that it was extremely hard to depict CAF by TTE, particularly in the cases having the left anterior descending coronary artery as the feeding vessel 6, 7, 9 . In addition, the CAF cases with the drainage site in the pulmonary artery were also reported to be difficult to fully detect by TTE, because the feeding coronary artery was not dilated 8, 10 .…”
Section: Discussionmentioning
confidence: 99%
“…Recent accumulating case reports have shown that multidetector computed tomography (MDCT) could be an alternative imaging modality of choice for CAF by its high temporal and spatial resolution power 1–3 . Although transesophageal echocardiography (TEE) has also been shown to be useful in the diagnosis of CAF, role of transthoracic echocardiography (TTE) in the diagnostic process for CAF remains controversial 4–10 . We describe our experience with three unusual cases of large CAF, in which TTE played a crucial role during the diagnostic process.…”
mentioning
confidence: 98%
“…Two dimensional echocardiography has its limitations in diagnosing coronary arteriovenous fistula but has been an important procedure in establishing the diagnosis in most cases 6)7). In our case, the proximal portion, the drainage site of coronary arteriovenous fistula, and the perforation of the posterior mitral leaflet were clearly demonstrated by two dimensional echocardiography.…”
Section: Discussionmentioning
confidence: 59%
“…vessel is sufficient, a conti nuous or turbul ent flow within the fistula or at the site of termination can be visualized by pulsed Doppler sonography (13)(14)(15). If the shunt volume is marked.…”
Section: Diagnos Ismentioning
confidence: 99%
“…In th e second so-called "d istal"form of CA F (type B) the coronary artery or a bran ch th ereof wa s dilated over th e entire course to finally termin at e as a fistu la w it hin th e righ t side of th e heart ("end ar te ry type", 12 ). Proxima l to the fistula a 14)of th e left coronary artery (LCA) to dra in into the right atr ium (patie nts 8,13,14) and/or into the coronary sinus (patients 13,15). In four add itional patient s (patients 9,10,1 1,12) the left anterior descend ing artery term inated into the right-vent ricular outfl ow tract afte r giving off normal diagonal branches (Fig.6 a, b).…”
Section: Ra ----->mentioning
confidence: 99%